2009
DOI: 10.2337/dc09-1352
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Continuous Glucose Monitoring in Critically Ill Patients

Abstract: OBJECTIVETo evaluate the impact of real-time continuous glucose monitoring (CGM) on glycemic control and risk of hypoglycemia in critically ill patients.RESEARCH DESIGN AND METHODSA total 124 patients receiving mechanical ventilation were randomly assigned to the real-time CGM group (n = 63; glucose values given every 5 min) or to the control group (n = 61; selective arterial glucose measurements according to an algorithm; simultaneously blinded CGM) for 72 h. Insulin infusion rates were guided according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
2
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 26 publications
2
157
2
9
Order By: Relevance
“…1). 20,25) The sensor is placed subcutaneously in the anterior abdominal wall and records the subcutaneous glucose concentration every 5 minutes. The recorder records these signals for up to 7 days, after which the data are uploaded to a computer and retrospectively analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…1). 20,25) The sensor is placed subcutaneously in the anterior abdominal wall and records the subcutaneous glucose concentration every 5 minutes. The recorder records these signals for up to 7 days, after which the data are uploaded to a computer and retrospectively analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The pinpoint of our study was not to ascertain the accuracy of current CGMS -we consider this question as being already solved by larger studies mentioned above [33][34][35][36][37][38][39][40][41] . We focused on glycaemia trends of operated patients, on identification of frequent patterns of glycaemic reaction to stress and on the determination of eventual CGM impact on glycaemic stability in individual cases.…”
Section: Hunger After the Surgerymentioning
confidence: 99%
“…Others found it useful for reducing hyperglycaemic episodes 35 . The analysis of two prospective randomized trials demonstrated clinically sufficient accuracy and safety 36,37 even in patients on vasopressors 38 . Some reject the use of subcutaneous sensors in the ICU setting 39,40 .…”
Section: Introductionmentioning
confidence: 95%
“…Preliminary work with continuous glucose measuring devices has demonstrated a dramatic reduction in the number of hypoglycemic episodes in critically ill patients. 27 For pharmacodynamic reasons, the rate of insulin infusion should not be titrated more rapidly than every 20 to 30 min. Most recent protocols mandate hourly measurements for patients in the ICU and every 30 to 60 min for patients undergoing major surgery.…”
Section: Sampling Frequencymentioning
confidence: 99%
“…Des travaux préliminaires réalisés avec des appareils de mesure continue de la glycémie ont montré une réduction spectaculaire du nombre d'épisodes d'hypoglycémie chez les patients gravement malades. 27 Pour des raisons pharmacodynamiques, la vitesse de perfusion d'insuline ne devrait pas être ajusté plus souvent que toutes les 20 à 30 minutes. La plupart des protocoles récents recommandent des mesures à toutes les heures chez les patients à l'USI et à des intervalles de 30 à 60 min chez les patients subissant une chirurgie majeure.…”
Section: Impact Cliniqueunclassified